'Start treating me like a Dad!' The impact of parental involvement in education on the paternal identity of fathers in the English prison system. Issue 2 (4th March 2019) - O'Keeffe, Helen
ABSTRACT: Notwithstanding the increasing number of UK and international studies focused on parental involvement in education and parental imprisonment there remains little focus upon the involvement of imprisoned fathers in children's education and the impact of this upon paternal identity. Despite the now accepted perspective that parental imprisonment often impacts negatively on family functioning, child outcomes and parental identity, this qualitative study is distinctive in drawing on the discourse of parental involvement in education, using the lens of identity theory to examine the experiences of 15 imprisoned fathers regarding their involvement in their children's education and their parenting possible selves as educators. Participants demonstrated limited identity standards in relation to education and sometimes a reduced commitment as a result of this. All offered a vision of their possible selves as educators if contextual barriers were addressed. Possible implications are suggested.